Broadening the Spectrum of Adulthood X-Linked Adrenoleukodystrophy: A Report of Two Atypical Cases - Foschi, Matteo; Vacchiano, Veria; Avoni, Patrizia; Incensi, Alex; Battaglia, Stella; Donadio, Vincenzo; Panzeri, Elena; Bassi, Maria Teresa; Liguori, Rocco; Rizzo, Giovanni (Frontiers in Neurology, 2019)
X-linked adrenoleukodystrophy (x-ALD) is a rare genetic disorder caused by mutation in ABCD1 gene which encodes for a peroxisomal very long chain fatty acids (VLCFA) transporter. Clinically, x-ALD can present with a wide spectrum of different phenotypes: asymptomatic carriers, Addison-only, cerebral x-ALD, myelopathy with/without evidence of peripheral axonopathy (adrenomyeloneuropathy). Our paper contains the description of two cases with atypical phenotypes: Case 1) A 37-year-old man presented with a 2-year-long history of urinary urgency and spastic paraparesis. Brain MRI showed posterior commissure agenesis, right fornix and mammillary body hypoplasia, colpocephaly, right frontal parasagittal cortical thickening, periventricular heterotropia. Case 2) A 64-year-old man presented with 7-year-long history of spastic paraparesis. 2 years later he complained of intense burning pain affecting both feet and markedly impairing his life quality. Skin biopsy revealed autonomic and somatic small fibers neuropathy (SFN). Both patients presented hypocortisolism and increased VLCFA levels while EMG resulted normal. Genetic testing disclosed in both cases heterozygous mutation in ABCD1 associated with x-ALD (A1394-2G, T254M respectively). In conclusion, we reported two adulthood x-ALD patients with atypical clinical features: 1) brain development defects, 2) clinically prevalent painful SFN with spared large myelinated peripheral fibers. While case 1 supports the key rule of peroxisome functions in brain development, case 2 suggests the possibility of a selective peripheral SF degeneration in x-ALD myelopathy.